Svitlana Kalenyuk. The addresses in internet communication: semantics and functional priorities. - Svitlana Kalenyuk (Philological Treatises, 2020)
The article is devoted to the problem of the determining of the semantic values and functions of addresses, which used in Internet communication. To achieve this aim, the author solves the following problems: explaining of the concept “Internet communication” and related terms, description of the problematic of the study the addresses’ semantics, because they are used with some deviations from linguistic norms, established rules of etiquette of spoken communication. The newest in the article is the streamlining of addresses recorded in Internet forums, Internet blogs and postal correspondence, on semantic fields and functions. In particular, it is defined that eight groups of vocabulary function in the semantic field of references for the designation of animate beings, and there are only four groups in the semantic field of applications for inanimate beings. They are united by functions of intimization or subordination of communication.